Le modèle centre-périphérie à l’épreuve : historicité et ancrage de la production artistique à Istanbul - Ilker Birkan; Jérémie Molho (Revue des Mondes Musulmans et de la Méditerranée)
The globalisation of the art world, while expanding the horizons of Western actors and observers towards new territories, focuses their attention on restricted times and spaces. The excitement for the vibrant art scene of Istanbul, where, in the last decade, numerous museums, fairs and galleries have emerged, tends to hide the historicity of artistic practices in Turkey. The few studies that integrate this historical perspective tend to argue that the history of “Turkish art” follows the evolution of global art. Against this universalized vision of art, this article proposes theoretical and methodological tools to better understand how the different ways of making and thinking art have been appropriated within art world organisations. Firstly, we draw on social history of artistic practices and of the art world, in order to identify aesthetical and organisational ruptures. Secondly, we show how lexicometric analysis and cartography enable to identify and situate different conventions within art worlds that coexist in contemporary times.